Reconstruction of the economy of the southern regions of the Ukrainian SSR and socio-economic revival of Crimea after the Second World War - Pavel Satsky (Facta Simonidis, 2020)
The research has provided an analysis of the social and economic situation on the Crimean Peninsula after the end of the World War Second, as well as on the territory of Ukrainian SSR neighboring to it. The obtained data as regards the situation with the economy and manpower resources of Crimea after the end of military operations and expulsion of indigenous peoples on its territory, as well as the social and economic situation of Kherson region and east regions of Ukraine provided the basis on which the main conditions of economic recreation of the Crimean region were studied. The materials were analyzed based on archive funds including business correspondence and statistical data of the state authorities in Ukrainian SSR and in the governing party (Ukrainian Communist Party of Bolsheviks) the bodies of which actually took all principal management decisions. The research showed that significant manpower and material resources were activated in southeast regions of Ukraine with the purpose of implementing large-scale projects in the industry and agriculture. The biggest attention was paid to development of power generation based on coal mining in Donets Basin and heat power generation in Dnipro Basin. Formation of powerful energy areas created conditions for development of systems for irrigating arid land in south regions of Ukraine, electrification of agriculture and formation of powerful industrial clusters in those regions of Ukraine that were neighboring to the Crimean Peninsula. Realization of large-scale projects of development in the regions, which were neighboring to territory of Crimea during the years of the first five-year plan implementation after the end of the World War Second created conditions for the economic recreation of Crimea through applying the experience and extending the territory scope of projects implementation to the territory of peninsula.